Counting ovarian antral follicles by ultrasound: a practical guide. (3rd January 2018) - Coelho Neto, M. A.; Ludwin, A.; Borrell, A.; Benacerraf, B.; Dewailly, D.; da Silva Costa, F.; Condous, G.; Alcazar, J. L.; Jokubkiene, L.; Guerriero, S.; Van den Bosch, T.; Martins, W. P.
ABSTRACT: This Consensus Opinion summarizes the main aspects of several techniques for performing ovarian antral follicle count (AFC), proposes a standardized report and provides recommendations for future research. AFC should be performed using a transvaginal ultrasound (US) probe with frequency ≥ 7 MHz. For training, we suggest a minimum of 20–40 supervised examinations. The operator should be able to adjust the machine settings in order to achieve the best contrast between follicular fluid and ovarian stroma. AFC may be evaluated using real‐time two‐dimensional (2D) US, stored 2D‐US cine‐loops and stored three‐dimensional (3D) US datasets. Real‐time 2D‐US has the advantage of permitting additional maneuvers to determine whether an anechoic structure is a follicle, but may require a longer scanning time, particularly when there is a large number of follicles, resulting in more discomfort to the patient. 2D‐US cine‐loops have the advantages of reduced scanning time and the possibility for other observers to perform the count. The 3D‐US technique requires US machines with 3D capability and the operators to receive additional training for acquisition/analysis, but has the same advantages as cine‐loop and also allows application of different imaging techniques, such as volume contrast imaging, inversion mode and semi‐automated techniques such as sonography‐based automated volume calculation. In this Consensus Opinion, we make certain recommendations based on the available evidence. However, there is no strong evidence that any one method is better than another; the operator should choose the best method for counting ovarian follicles based on availability of resources and on their own preference and skill. More studies evaluating how to improve the reliability of AFC should be encouraged. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.